Comparative effectiveness of tocilizumab and TNF inhibitors in rheumatoid arthritis patients - Romão, Vasco C. (2017)
Objectives. To compare the effectiveness of TNF inhibitors (TNFi) and tocilizumab in rheumatoid arthritis (RA) treatment, according to different response criteria. Methods. We included RA patients registered in the Rheumatic Diseases Portuguese Register treated with TNFi or tocilizumab for at least 6 months, between January 2008 and July 2013. We assessed remission/low disease activity (LDA) at 6 months according to DAS28, CDAI, and SDAI, as well as Boolean ACR/EULAR remission and EULAR response rate, adjusting for measured confounders. Results. Tocilizumab-treated patients (n = 95) presented higher baseline disease activity and were less frequently naïve to biologics compared to TNFi users (n = 429). Multivariate logistic regression analysis including the propensity score for receiving tocilizumab showed that patients treated with tocilizumab were more likely to achieve remission or LDA according to DAS28 (OR = 11.0/6.2, 95% CI 5.6-21.6/3.2-12.0), CDAI (OR = 2.8/2.6, 95% CI 1.2-6.5/1.3-5.5), or SDAI (OR = 3.6/2.5, 95% CI 1.5-8.7/1.1-5.5), as well as a good EULAR response (OR = 6.4, 95% CI 3.4-12.0). However, both groups did not differ in Boolean remission (OR = 1.9, 95% CI 0.8-4.8) or good/moderate EULAR response (OR = 1.8, 95% CI 0.8-4.5). Conclusions. Compared with TNFi, tocilizumab was associated with greater likelihood of achieving DAS28, CDAI, and SDAI remission/LDA and EULAR good response. Boolean remission and EULAR good/moderate response did not differ significantly between groups.